Perspectivas para o jornalismo crítico de games - Assis, Diego O. de (2007)
The goal of this study is to analise the actual stage of games journalism and point to new perspectives regarding its critical approach. Even though recognized as one of the most promising sectors of the entertainment industry in the new millenium, the universe of the videogames is still receiving a not so representative attention from the mass communication vehicles if compared to more traditional forms such as cinema and music. Nowadays, a great portion of the coverage of videogames is still confined to specialized publications and technology sections of newspapers and magazines. To pursue this analysis it will at first be necessary to trace a historical panorama of the development of electronic games. Created almost 50 years ago, in an atempt to turn computers into something fun, videogames have been gaining complexity with successive technological advances until they have transformed into one of the most intriguing cultural objects from the turn of the 20th to the 21st century. Present in the lives of young people from all kind of societies in the last two decades, games have started to influence and to be influenced by other aesthetical languages from the pop culture, like movies, music, cartoons and comic books. Today, as stated by authors such as Chris Crawford, Steven Poole and Henry Jenkins, games represent a new and autonomous cultural cathegory, with specific features that demand its own theories and concepts. After going into the cultural and technological evolution of videogames, we will then look at some of the main publications dedicated to the subject, including segmented magazines, like Electronic Gaming Monthly, news and reviews websites, such as GameSpot.com and IGN.com, and blogs and internet services that have recently joined what is called games journalism. Still on this issue, we intend to show the major problems faced by games journalism in order to refrain from performing a mere utilitary role which it traditionally did and start dealing with the cultural, social and economical layers that have stick to the universe of videogames in the last decades. (Something that, paradoxically, publications of the non-specialized media, such as The New York Times and Wired have performed way more efficiently.) At last, we will be listing a few examples of how a well-informed games criticism practice can benefit from literature, as is the case with the controversial new games journalism, and also from concepts that are being debated in the Academy such as narrative (Murray), simulation (Frasca), meaningful play (Salen and Zimmerman) and software (Galloway, Manovich)